Any short method to solve this type of question.? No copied solution.
![](https://hi-static.z-dn.net/files/d69/ad26c9ff7ce729ecf23318af4af5920c.jpg)
Answers
Step-by-step explanation:
just substitute the x value with its derivatives in the equation, then u will get zero.
ex : y = c1 e^ax cos bx + c2 e^ax sin bx
dy/dx = a ( c1 e^ax cos bx + c2 e^ax sin bx ) + b ( c2 e^ax cos bx - c1 e^ax sin bx )
i,e.. dy/dx = ay + b ( c2 e^ax cos bx - c1 e^ax sin bx )
now....
d^2y/dx = a y' + ba ( c2 e^ax cos bx - c1 e^ax sin bx ) - b×b ( c1 e^ax cos bx + c2 e^ax sin bx )
i,e...d^2y/dx = a (y') + a(y' - ay)- b^2 (y)
d^2y/dx = 2a y' - (a^2 + b^2) y
finally.....
d^2/dy - 2a dy/dx + (a^2 + b^2)y =
= [ 2a y' - (a^2 + b^2) y ] [ 2a y' ] - (a^2 + b^2) y
= 2a y' - (a^2 + b^2) y - 2a y' + (a^2 + b^2) y
= 0
Formula used:
d/dx(e^ax)= a (e^ax)
d/dx (cos ax)= a (-sinax)
d/dx(sin ax) = a (cosax)
d/dx (u•v) = u d/dx(v) +v d/dx(u)
Solution refer to the attachment..
![](https://hi-static.z-dn.net/files/dd3/29dd995ad9bc83224e43945b43fcb745.jpg)